Neonatal leukemia and maternal irradiation - Say, Burhan; Şenocak, Gülseren (The Turkish Journal of Pediatrics, 1961)
The authors report views of leukemia in newborn infants and a case is presented in which the mother received radiation during pregnancy. It is concluded that this irradiation might be an etiologic factor in this case of neonatal leukemia.